Cover Image, Volume 26, Issue 6. (10th May 2018) - Harvey, Steven P.; Moseley, John; Norman, Andrew; Stokes, Adam; Gorman, Brian; Hacke, Peter; Johnston, Steve; Al‐Jassim, Mowafak
Abstract : The cover image, by Steven P. Harvey et al., is based on the Research Article Investigating PID shunting in polycrystalline silicon modules via multiscale, multitechnique characterization, DOI:10.1002/pip.2996 .